Persistence of Ascaris spp. Ova in Tropical Soil Cultivated with Eucalyptus and Fertilized with Municipal Biosolids - Faria, Marianne F. de [UNESP]; Guerrini, Irae A. [UNESP]; Oliveira, Fernando C.; Sato, Maria Ines Z.; Hachich, Elayse M.; Passos, Jose Raimundo S. [UNESP]; Goulart, Livia M. L. [UNESP]; Silva, Thiago T. de S. [UNESP]; Gava, Jose L.; Furches, Joel C.; James, Jason; Harrison, Robert B. (Amer Soc Agronomy, 2017)
In many countries, the main reason for severely restricting or outright banning the land application of class B biosolids is the lack of risk assessment for adverse human health impacts. Among pathogens that are not often studied are helminth ova, including that of the Ascaris spp. Almost all of the knowledge about the persistence of Ascaris spp. ova in soils fertilized with biosolids is based on studies developed in North America, Europe, and Asia. These studies have almost always been conducted under temperate climate conditions, which may cause erroneous interpretations when the conclusions are extrapolated to tropical regions such as those found in Brazil. This team evaluated the persistence of viable Ascaris spp. ova in a sandy Quartzipsamment tropical soil, previously planted with Eucalyptus urophylla x Eucalyptus grandis hybrid ( Eucalyptus urograndis) and fertilized with biosolids, over a 52-wk period. During the reporting period, the average temperature of soil and biosolids fluctuated between 15 and 30 degrees C, and the average moisture of biosolids fluctuated between 60 and 90%. The estimated persistence time of viable Ascaris spp. ova after land application was estimated at close to 7 wk, indicating that ova may not be viable for as long as it has been shown to be in studies of more temperate areas. The relationship of temperature with persistence of viable Ascaris spp. ova in a tropical soil was stronger than moisture content, suggesting that temperature substantially contributed to their nonviability over the course of the experiment.